2006
DOI: 10.1124/jpet.106.103184
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Phospholipid Derivative of Indomethacin, DP-155 [Mixture of 1-Steroyl and 1-Palmitoyl-2-{6-[1-(p-chlorobenzoyl)-5-methoxy-2-methyl-3-indolyl acetamido]hexanoyl}-sn-glycero-3-phosophatidyl Choline], Shows Superior Safety and Similar Efficacy in Reducing Brain Amyloid β in an Alzheimer's Disease Model

Abstract: Indomethacin has been suggested for the treatment of Alzheimer's disease (AD), but its use is limited by gastrointestinal and renal toxicity. To overcome this limitation, D-Pharm Ltd. (Rehovot, Israel) developed DP-155 (mixture of 1-steroyl and 1-palmitoyl-2-{6-[1-(p-chlorobenzoyl)-5-methoxy-2-methyl-3-indolyl acetamido] hexanoyl}-sn-glycero-3-phosophatidyl choline), a lecithin derivative of indomethacin. Safety was tested by daily oral administration of DP-155 or indomethacin to rats in a dose range of 0.007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…At 15 months of age, the SDS-extractable A␤ represents approximately 10% of the A␤ pool extracted by FA (Kawarabayashi et al, 2001). Because ␥-secretase modulators are thought to mainly affect SDS-extractable A␤ pools, i.e., the newly formed A␤ (Yan et al, 2003;Dvir et al, 2006), a double SDS extraction was performed in an attempt to maximize this A␤ fraction. Indeed, the double SDS-extracted A␤ in our study represented 46 to 47% of the total extracted A␤.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 15 months of age, the SDS-extractable A␤ represents approximately 10% of the A␤ pool extracted by FA (Kawarabayashi et al, 2001). Because ␥-secretase modulators are thought to mainly affect SDS-extractable A␤ pools, i.e., the newly formed A␤ (Yan et al, 2003;Dvir et al, 2006), a double SDS extraction was performed in an attempt to maximize this A␤ fraction. Indeed, the double SDS-extracted A␤ in our study represented 46 to 47% of the total extracted A␤.…”
Section: Discussionmentioning
confidence: 99%
“…A␤40 and A␤42 were extracted from brain by using both the SDS and formic acid (FA) methods. Because ␥-secretase modulators are thought to affect mainly SDS-extractable A␤ pools, i.e., the newly formed A␤ (Yan et al, 2003;Dvir et al, 2006), a double SDS extraction was performed in an attempt to maximize SDS-extractable A␤. One hemisphere was first homogenated in 2% SDS in water [100 mg/ml (wet w/v)] containing protease inhibitors (Complete Protease Inhibitor Cocktail; Roche Diagnostics, Basel, Switzerland) and an aliquot of 500 l was centrifuged at 16,000g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of indomethacin to block COX activity, which may help to mitigate endothelial injury in response to hypoxia (Gloria et al 2006), may provide an additional reason for its inclusion in the construct. Furthermore, it has been shown that DP-155 selectively inhibits the inducible COX-2 but not the constitutively active COX-1 (Dvir et al 2006), a property that may further contribute to the selective anti-inflammatory effects of the drug.…”
Section: Discussionmentioning
confidence: 98%
“…One approach to reduce the adverse effects of NSAIDs is the use of a prodrug strategy (Rodriguez-Tellez et al 2001). We took advantage of a newly developed indomethacin prodrug (DP-155; Dvir et al 2006) to study its effects on the 31 P MRS phospholipid profile of ECs grown in 3D Matrigel threads. DP-155 ( Figure 3A) consists of the parental drug indomethacin ( Figure 3B) coupled through a lipidic linker (DP-499; Figure 3C) to phosphatidylcholine (PtdC; Figure 3D).…”
Section: Dp-155 a Lipid Prodrug Of Indomethacin Mimics The Effects mentioning
confidence: 99%
See 1 more Smart Citation